A clinical study of cutaneous changes in pregnancy. Issue 1 (March 2017) - Panicker, Vinitha V.; Riyaz, Najeeba; Balachandran, P.K.
Abstract: Background/objective: Pregnant women experience a myriad of physiological and metabolic changes that affect different organ systems in the body. Cutaneous and appendageal alterations that manifest during pregnancy are largely modulated by hormonal, immunologic, and metabolic factors. Detailed reports encompassing physiological changes and specific dermatoses of pregnancy and effects of various dermatoses on pregnant women are scanty in literature. This study was conducted to examine in detail both physiological changes and specific dermatoses. The cutaneous changes are divided into physiological changes, skin diseases aggravated by pregnancy, and specific dermatoses of pregnancy. The objectives were to study the various cutaneous changes of pregnancy and to know the proportion of these cutaneous manifestations in pregnant women. Methods: This study included 600 pregnant women attending the Obstetrics and Gynecology Department of a tertiary teaching hospital in Northern Kerala, India. Detailed history elicitation and complete physical and dermatological examination were performed. Skin biopsy was performed in relevant cases. Results: Cutaneous changes were seen in a majority of patients, of which physiological changes were the most common (99%). The most common cutaneous manifestation was hyperpigmentation (526; 87.6%), followed by striae gravidarum (72.8%). Other changes were vascular, including pedal edema (10%), pregnancy gingivitis (1.8%), and varicose veins (1%). Infections were the common dermatological problem in this study group. The most common infections were vulvovaginal candidiasis (21%), Tinea versicolor (6%), scabies (2.8%), dermatophytosis (1.5%), and sexually transmitted infection (0.5%). Specific dermatoses were seen in 12 cases (2%), with the most common being pruritic urticarial papules and plaques of pregnancy (1.3%). Conclusion: Pregnant women are prone to suffer from a wide range of dermatological problems apart from specific dermatoses of pregnancy. The study emphasizes the need for a detailed and meticulous examination of these patients to detect these various disorders.